Dose Dependent Antimicrobial Cellular Cytotoxicity—Implications for ex vivo Diagnostics - Copaescu, Ana; Choshi, Phuti; Pedretti, Sarah; Mouhtouris, Effie; Peter, Jonathan; Trubiano, Jason A. (Frontiers in Pharmacology, 2021)
Please refer to text in the manuscript